Bahasa Inggris: Bahasa Inggris (Jurnal Ekonomi Pembangunan Widya Mandira, 2025)
Environmental, Social, and Governance (ESG) factors have emerged as critical drivers of sustainable economic growth in recent decades. This systematic literature review examines the interplay between ESG practices and economic growth, focusing on regional and sectoral differences, methodological approaches, and key findings from empirical studies. Using PRISMA guidelines, this review analyzes 23 peer-reviewed articles published between 2014 and 2024. The findings indicate that ESG significantly contributes to economic growth by attracting foreign direct investment (FDI), enhancing corporate financial performance, and fostering sustainability. However, the impact varies across regions, with notable differences between developed and developing countries. This study highlights the importance of integrating ESG principles into national and corporate strategies to achieve long-term economic resilience.
Keywords: Bahasa Inggris